1994
DOI: 10.1677/joe.0.1430441
|View full text |Cite
|
Sign up to set email alerts
|

The role of prolactin in the reactivation of hair follicles in relation to moulting in cashmere goats

Abstract: The effects of the suppression or elevation of plasma prolactin concentrations in spring on the timing of the reactivation of the hair follicles and the timing of the spring moult were investigated in cashmere goats. Thirty eight adult female goats, housed under conditions of natural photoperiod at 55 degrees 55'N from mid-December until May, were allocated to four groups starting on 5 January: ten served as untreated controls, eight received 2 mg ovine prolactin subcutaneously every 12 h for 7 weeks (PRL), tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 11 publications
3
38
1
Order By: Relevance
“…Earlier studies showed that changes in circulating prolactin can trigger hair cycle progression (Pearson et al 1993, Dicks et al 1994, but it has been unclear how this hormone can exert apparently opposite influences at different phases of the cycle. The close association between the level of PRLR mRNA in the skin and follicle growth status suggests that cellular activity in the follicle is related to receptor abundance and the consequent level of signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that changes in circulating prolactin can trigger hair cycle progression (Pearson et al 1993, Dicks et al 1994, but it has been unclear how this hormone can exert apparently opposite influences at different phases of the cycle. The close association between the level of PRLR mRNA in the skin and follicle growth status suggests that cellular activity in the follicle is related to receptor abundance and the consequent level of signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Cashmere growth exhibits a seasonal rhythm (Dicks et al, 1994;Klören & Norton, 1995;Santiago-Moreno et al, 2004). Research has shown that melatonin is a critical intermediary between photoperiod and cashmere growth with circulating melatonin levels directly affecting cashmere growth (Teh et al, 1991;Klören & Norton, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal cashmere growth cycles in Inner Mongolian cashmere goats have been well defined with outgrowth on the surface in August and ceases in following February with shedding of the fleece at the end of April, and the nongrowing period for cashmere is from March to July (Da et al 1991). Cashmere growth exhibits a seasonal rhythm arising from circannual changes in the natural photoperiod (Klören and Norton 1993;Dicks et al 1994;Santiago-Moreno et al 2004). Melatonin is a critical intermediary between the photoperiod and cashmere growth (Teh et al 1991).…”
Section: Introductionmentioning
confidence: 99%